Social anxiety among students of socio-humanitarian areas of professional training - N. A. Tsvetkova (Вестник университета)
The subject of the study is social anxiety, the purpose is to determine its prevalence and severity in students of socio-humanitarian training areas.   The principles of socio-psychological approach, methodology and method of socio-psychological diagnostics of social anxiety and social phobia by O. A. Sagalkova and D. V. Truyavtsev were used. The genera lized index of social anxiety (48.1 points), which corresponds to an elevated level with a tendency to high, has been determined. The dominant type of social phobia such as “Post-situational rumination and desire to overcome anxiety in expert situations” has been identified, the index of which (6.84 stens) tends to a high level. Students with this type of social anxiety make up the largest sharein the sample (48.13 %). Three groups of students have been identified and characterized: students with indicators of clinical social phobia and clinical social phobia in decompensation (about 20 % of the sample); students with elevated and high levels of social anxiety (slightly more than 50 %); students with low and moderate levels of social anxiety (slightly less than 30 %). Obtained results application score: higher school psychology; applied and practical social psychology; social protection system psychologists, clinical psychologists, medical psychologists, and psychiatrists. Prospects of the study is social anxiety monitoring in students of Russian universities. The study results confirmed the need for social anxiety monitoring in students of socio-humanitarian areas of professional training, about 50 % of whom to a greater or lesser extent need socio-psychological help, and about 20 % of whom need psychiatric help.